Sleep medicine. Issue 3 (June 2015) - Cornfield, David N.; Bhargava, Sumit
<x xml:space="preserve">Abstract</x> Purpose of review Sleep medicine is an increasingly well subscribed component of pediatric medicine. While knowledge has increased significantly in the past five decades, whether the most widely used tool to assess sleep-disordered breathing possesses demonstrable clinical utility remains unknown. The absence of certainty surrounding the impact of polysomnography (PSG) testing on clinical outcomes, superimposed on the cost and inconvenience of PSG testing, prompts a call to reassess the current normative stance toward PSG testing. Recent findings The present study argues for the use of the following: endpoints that have known clinical significance; readily available data provided by parents; and data derived from a randomized, placebo-controlled trial to determine the merits of PSG testing in the context of obstructive sleep apnea. Summary By rationalizing the use PSG testing, cost, inconvenience, and parental anxiety can be decreased without compromising care.